Turbulent particle transport as a function of toroidal rotation in DIII-D H-mode plasmas. (1st March 2016) - Wang, X; Mordijck, S; Zeng, L; Schmitz, L; Rhodes, T L; Doyle, E J; Groebner, R; Meneghini, O; Staebler, G M; Smith, S P
Abstract: In this paper we show how changes in toroidal rotation, by controlling the injected torque, affect particle transport and confinement. The toroidal rotation is altered using the co- and counter neutral beam injection (NBI) in low collisionality H-mode plasmas on DIII-D (Luxon 2002 Nucl. Fusion 42 614) with dominant electron cyclotron heating (ECH). We find that there is no correlation between the toroidal rotation shear and the inverse density gradient, which is observed on AUG when is varied using ECH (Angioni et al 2011 Phys. Rev. Lett .107 215003). In DIII-D, we find that in a discharge with balanced torque injection, the shear is smaller than the linear gyrokinetic growth rate for small for –0.85. This results in lower particle confinement. In the co- and counter- injected discharges the shear is larger or close to the linear growth rate at the plasma edge and both configurations have higher particle confinement. In order to measure particle transport, we use a small periodic perturbative gas puff. This gas puff perturbs the density profiles and allows us to extract the perturbed diffusion and inward pinch coefficients. We observe a strong increase in the inward particle pinch in the counter-torque injected plasma. Finally, the calculated quasi-linear particle flux, nor the linear growth rates using TGLF (Staebler et al 2005 Phys. Plasmas 12 102508) agree with experimental observations.